Using Hourly Time-Outs and a Standardized Tool to Promote Team Communication, Medical Record Documentation, and Patient Satisfaction During Second-Stage Labor. Issue 4 (July 2018) - Wood, Jessica; Stevenson, Eleanor
Abstract: Background: During labor, effective communication and collaboration among the healthcare team is critical for patient safety; however, there is currently no standard for communication and documentation of the plan of care as agreed upon by healthcare team members and the woman in labor. Objectives: The goal of this project was to increase consistency in communication and collaboration between clinicians and laboring women during second-stage labor. Methods: An hourly "time-out" meeting of all healthcare team members was initiated for all women during second-stage labor. A documentation tool was implemented to ensure regular and clear communication between the clinical team and laboring women. Data were collected via medical review of cases of second-stage labor lasting more than 2 hours (n = 21 in the pre-implementation group; n = 39 for 3 months postimplementation; and n = 468 patients for 2 years post-implementation). Surveys were conducted of the clinical team (n = 40) and patients ( n = 28). Results: Following implementation, documented agreement of the plan of care increased from 14.3% before the project to 82.1% 3 months after implementation and remained at 81.6% 2 years after implementation. All nurses who participated in the survey reported a clear understanding of how and when to complete necessary medical record documentation during second-stage labor. The providers viewed the project favorably. Most women (92.9%) reported satisfaction with their experience. This project enhanced collaborative communication between members of the clinical team and laboring women and improved patient satisfaction. The improvements were sustainable over a 2-year period. Abstract : This quality improvement project focused on a standardized process for medical record documentation and for communication among clinical team members and the laboring woman during second stage labor. A key aspect was an hourly time-out beginning at the start of second stage labor. Findings suggest these methods collectively can improve medical record documentation, enhance patient satisfaction, and promote patient safety.